Rubber : Science and Technology - Princi, Elisabetta (De Gruyter STEM, 2019)
Rubber materials serve a variety of purposes in our everyday life. This book gives a complete survey of the life cycle of rubber materials starting from the basics and covering everything to recycling of rubber. The important aspects for researchers and engineers in rubber industry such as vulcanization, thermoplastic elastomers, additives and fillers and rubber bonding is covered in one chapter each.